Kinetic Resolution of Unsymmetrical Acyclic Allyl Carbonates Using Trimethylsilyl Cyanide via Palladium-Catalyzed Asymmetric Allylic Alkylation - Bai, Da-Chang; Wang, Wan-Ying; Ding, Chang-Hua; Hou, Xue-Long (Synlett, 2015)
The kinetic resolution of 1,3-disubstituted unsymmetrical allylic substrates with TMSCN as the nucleophile was realized via palladium-catalyzed asymmetric allylic alkylation, providing optically active allylic substrates and β,γ-unsaturated nitriles in good yield and enantioselectivity.
Keywords: kinetic resolution; palladium; asymmetric allylic alkylation; unsymmetrical acylic allyl carbonates; trimethylsilyl cyanide